2019
DOI: 10.31629/jg.v4i2.1560
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning Syarah: Bagaimana Penerapan dan Persepsi Mahasiswa

Abstract: This study aims to see how the implementation and students’ perceptions of e-learning type blended learning in Mathematics Capita Selecta course. The e-learning in this study utilized the Syarah portal, an online learning application developed by Universitas Maritim Raja Ali Haji (UMRAH) responding to the 4.0 era. This online learning using Syarah was the first time applied to research subjects, namely 35 students of Mathematics Capita Selecta Course year 2019. The data was collected from the results of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 0 publications
1
15
1
22
Order By: Relevance
“…Meanwhile, in their research, (Astuti & Febrian, 2019) found that students respond positively to online learning. Students feel more comfortable doing questions and answers in an online learning pattern than in face-to-face classes.…”
Section: Students Perception Towards Online Learningmentioning
confidence: 99%
“…Meanwhile, in their research, (Astuti & Febrian, 2019) found that students respond positively to online learning. Students feel more comfortable doing questions and answers in an online learning pattern than in face-to-face classes.…”
Section: Students Perception Towards Online Learningmentioning
confidence: 99%
“…Sebagian besar peserta pelatihan pertanian memang berada di wilayah perdesaan yang jangkauan sinyal internetnya masih lemah. Argumentasi ini juga didasarkan pada hasil penelitian dari (Astuti & Febrian, 2019) bahwa kekurangan pembelajaran daring ketika layanan internet lemah dan diperparah oleh penyajian materi yang sulit dipahami. Sinyal internet yang lemah dan biaya paket data kuota internet yang besar menjadi tantangan tersendiri dalam pembelajaran daring (Munajatisari;, 2014) Kendala yang dialami dalam pelaksanaan pelatihan online adalah masalah jaringan internet dan kuota .…”
Section: Gambar 1 Masalah Pelatihan Onlineunclassified
“…If the internet connection is low then it will become certain challenge for the teacher or the students. Online learning has weakness when the internet connection is low, and the teacher's instruction is less understood by the students [12].…”
Section: Facilities Used In Online Learningmentioning
confidence: 99%